2014
DOI: 10.1002/acn3.153
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Yeasts Reduce Inflammation in Central Nerve System via Microflora

Abstract: ObjectivesThe intestinal microflora affects the pathogenesis of several autoimmune diseases by influencing immune system function. Some bacteria, such as lactic acid bacteria, have been reported to have beneficial effects on immune function. However, little is known about the effects of yeasts. Here, we aimed to investigate the effects of various dietary yeasts contained in fermented foods on experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), and to elucidate the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…It has also been reported in an animal model that S. boulardii interacts with and alters commensal bacterial microbiota (Yu et al, 2017) (Figure 1). Similarly, a recent study demonstrated that oral administration of the dietary yeast Candida kefyr (also known as Candida pseudotropicalis or Kluyveromyces marxianus ) was protective in mouse models of colitis and experimental autoimmune encephalomyelitis (Takata et al, 2015). This was accompanied by alterations in the bacterial microbiota, and transfer of the microbiota into new animals could confer protection that was associated with an increase in mesenteric lymph node regulatory T cells and reduction in lamina propria Th17 cells.…”
Section: Prospects For Therapeutic Manipulation Of Fungal Communitiesmentioning
confidence: 99%
“…It has also been reported in an animal model that S. boulardii interacts with and alters commensal bacterial microbiota (Yu et al, 2017) (Figure 1). Similarly, a recent study demonstrated that oral administration of the dietary yeast Candida kefyr (also known as Candida pseudotropicalis or Kluyveromyces marxianus ) was protective in mouse models of colitis and experimental autoimmune encephalomyelitis (Takata et al, 2015). This was accompanied by alterations in the bacterial microbiota, and transfer of the microbiota into new animals could confer protection that was associated with an increase in mesenteric lymph node regulatory T cells and reduction in lamina propria Th17 cells.…”
Section: Prospects For Therapeutic Manipulation Of Fungal Communitiesmentioning
confidence: 99%
“…In our study, oral administration of C. kefyr reduced the proportion of Bacteroides and microbiome transfer from C. kefyr ‐treated mice reduced the proportion of Bacteroides and ameliorated EAE and dextran sulfate sodium‐induced colitis. However, oral administration of S. cerevisiae did not reduce the proportion of Bacteroides or clinical severities in both animal models 2. These results suggested that modification of microbiome by C. kefyr reduced inflammation.…”
mentioning
confidence: 83%
“…Diet, intestinal microflora, and metabolites produced by this microflora are important because they exert positive effects on human health through intestinal immunity. Several bacteria and their components exert positive effects against experimental autoimmune encephalomyelitis (EAE); however, limited information is available on the effects of yeasts such as Saccharomyces , Candida , and Aspergillus , which are constituents of fermented foods, on EAE 2. Our study is significant because we found that Candida kefyr ameliorated EAE; in addition, our study suggested that not all yeasts exerted the same effect on immunity, as mentioned by Perricone et al Furthermore, the effects of C. kefyr seem to be some immune‐mediated diseases specifically depending on the underlying pathology.…”
mentioning
confidence: 99%
“…may have revealed the importance of different dietary yeast in contribution to inflammation and autoimmunity. From one side, it is possible that some types (such as Saccharomyces boulardii ) can be used as probiotics acting in a microbiome competition model leading to amelioration of autoimmune conditions 1. Nonetheless, it is fundamental to address the exact role of those types which, on the contrary, may even worsen an autoimmune/inflammatory condition.…”
mentioning
confidence: 99%
“…We recently read with great interest the article on the possible immunomodulatory effects of dietary yeast, specifically Candida kefir, on the central nervous system, notably the experimental autoimmune encephalomyelitis (EAE) mouse model by Takata et al 1 The role of yeast in inflammatory and autoimmune phenomena is nowadays controversial. 2 The experiment from Takata et al raises an important observation that not all yeast lead to the same effect on immunity.…”
mentioning
confidence: 99%